The Reliability and Validity of the 3-min All-out Cycling Critical Power Test - Wright, James; Bruce-Low, Stewart; Jobson, Simon A. (International Journal of Sports Medicine, 2017)
Research suggests that critical power (CP) can be estimated from a single 3-min bout of all-out cycling. The purpose of this study was to investigate the reliability and validity of the 3-min all-out cycling test when carried out at a constant cadence (isokinetic) and against a fixed resistance (linear). 12 participants completed 8 tests: 1) a ramp test; 2–4) 3 fixed power tests to calculate CP and W′ using the 1/time mathematical model; 5–8) four 3-min all-out tests to calculate EP and WEP; 2 isokinetic and 2 linear tests. There was no significant difference between EP-isokinetic and CP (P=0.377). There were significant differences between EP-linear and CP (P=0.004), WEP-isokinetic and W′ (P<0.001) and WEP-linear and W′ (P<0.001). The coefficient of variation in EP-isokinetic, EP-linear, WEP-isokinetic and WEP-linear was 1.93, 1.17, 8.44 and 5.39%, respectively. The 3-min all-out isokinetic test provides a reliable estimate of EP and a valid estimate of CP. The 3-min all-out linear test provides a reliable estimate of EP, but not a valid estimate of CP. Furthermore, these results suggest that the 3-min all-out test should not be used to estimate W′.
Keywords: exercise testing; anaerobic capacity; training zones; isokinetic